Effects of cavernous nerve reconstruction on expression of nitric oxide synthase isoforms in rats - Schlenker, Boris Alexander; Matiasek, Kaspar; Saur, Dieter; Gratzke, Christian; Bauer, Ricarda M.; Herouy, Yared; Arndt, Christian; Blesch, Armin; Hartung, Rudolf; Stief, Christian G.; Weidner, Norbert; May, Florian (BJU international, 2010)
To evaluate the expression of nitric oxide synthase (NOS) isoforms after various reconstruction techniques in rats, to improve the understanding of neuronal repair mechanisms after radical prostatectomy, as Schwann cell-seeded guidance tubes have been shown to promote cavernous nerve regeneration, and glial cell-line-derived neurotrophic factor (GDNF)-overexpressing Schwann cells enhance nerve regenerative capacity.
Gesehen am 13.06.2023